Pornography and the justices the Supreme Court and the intractable obscenity problem - Hixson, Richard F. (Southern Illinois Univ. Press, 1996)
What sets Pornography and the Justices apart from other studies of pornography is its unique focus and its fresh conclusion, which is a composite of views garnered from the Supreme Court justices. As long as the government does not discriminate against specific points of view and as long as there is ample protection of minors and nonconsenting adults, Hixson argues that the private collection of pornography is up to the individual. Hixson contends that the freedom to purchase obscene pornographic matter should be restricted only by time, place, and manner considerations. If a person wants pornography, he or she should be able to get it, albeit perhaps from a higher shelf, in a secluded room, or at a theater clearly marked for adults. Hixson sees no need to legislate personal morals beyond controlling public access